The effect of family appraisal on caregiver burden in family caregiver of female cancer patients - Ni Putu Wulan Purnama Sari; Maria Manungkalit (Intelektual Pustaka Media Utama, 2023)
The growing prevalent of female cancer malignancies and the cancer care transition from clinical-based into home-based care have resulted in the growing involvement of family caregiver (FCG) in cancer management. The caregiving activity may be appraised as positive or negative life aspect. Negative family appraisal may result in FCG burden. This study expected to examine the effect of FCG appraisal of cancer caregiving on their burden in community context. This cross-sectional study involved 60 FCG of female cancer patients in five communities of Surabaya. Population was all primary FCG of female cancer patients in Surabaya’s communities. Family appraisal and caregiver burden were measured by questionnaires of family appraisal of caregiving questionnaire for palliative care (FACQ-PC) and caregiver burden inventory (CBI) respectively. Data analysis utilized descriptive statistic and simple linear regression tests. Most respondents were spouses with very mature age (41-50 years old), high school graduated, and working with sufficient income. The majority appraised cancer caregiving activities positively (80.67±16.31) and reported low burden (32.02±12.23). FCG appraisal has a huge impact on their burden (p=0.000). It influences 20.7% variance of burden in this population (R2=0.207).